If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+2)-x=4(x-4)+4
We move all terms to the left:
6(x+2)-x-(4(x-4)+4)=0
We add all the numbers together, and all the variables
-1x+6(x+2)-(4(x-4)+4)=0
We multiply parentheses
-1x+6x-(4(x-4)+4)+12=0
We calculate terms in parentheses: -(4(x-4)+4), so:We add all the numbers together, and all the variables
4(x-4)+4
We multiply parentheses
4x-16+4
We add all the numbers together, and all the variables
4x-12
Back to the equation:
-(4x-12)
5x-(4x-12)+12=0
We get rid of parentheses
5x-4x+12+12=0
We add all the numbers together, and all the variables
x+24=0
We move all terms containing x to the left, all other terms to the right
x=-24
| 14=n/5+6 | | –7p–9=–3+3(p–2) | | 2/7y+5=(-9) | | 8x-17=9x-9 | | 2x+(x-5)=1 | | (y+8)(y+29)=0 | | -5x-2=-x+18 | | 7v+15=4v+33 | | 2x+x-5=1 | | 18.2+2y=6y+7 | | 2+(3x+1)=5x+7 | | 4w+1=8w+17 | | 4/6x-3/6=2/6+5/6x | | 3×(x-6)=2×(x-7) | | 3u+20=7u-12 | | z÷3=2 | | 2x-2+3x-3=18 | | 964=n+34 | | 2x+15=25-4x | | t/24=27 | | t÷24=27 | | 2×(x+1)=2x+10 | | 4(b+3)+2b=3(b-11) | | 17c=935 | | 289=y+464 | | t+55=68 | | q+46=95 | | 4×(x-5)=-12 | | -4y=928 | | 219=w+-650 | | 36=r+30 | | q-7.67=20.34 |